Estimating minimally important difference (MID) in PROMIS pediatric measures using the scale-judgment method - Thissen, David; Liu, Yang; Magnus, Brooke; Quinn, Hally; Gipson, Debbie S.; Dampier, Carlton; Huang, I-Chan; Hinds, Pamela S.; Selewski, David T.; Reeve, Bryce B.; Gross, Heather E.; DeWalt, Darren A. (Quality of life research, 2016)
Objective To assess minimally important differences (MIDs) for several pediatrie self-report item banks from the National Institutes of Health Patient-Reported Outcomes Measurement Information System® (PROMIS®). Methods We presented vignettes comprising sets of two completed PROMIS questionnaires and asked judges to declare whether the individual completing those questionnaires had an important change or not. We enrolled judges (including adolescents, parents, and clinicians) who responded to 24 vignettes (six for each domain of depression, pain interference, fatigue, and mobility). We used item response theory to model responses to the vignettes across different judges and estimated MID as the point at which 50 % of the judges would declare an important change. Results We enrolled 246 judges (78 adolescents, 85 parents, and 83 clinicians). The MID estimated with clinician data was about 2 points on the PROMIS T-score scale, and the MID estimated with adolescent and parent data was about 3 points on that same scale. Conclusions The MIDs enhance the value of PROMIS pediatric measures in clinical research studies to identify meaningful changes in health status over time.